review on recent research results (2008–2010) on essential oils as antimicrobials and antifungals. A review - Lang, Gudrun; Buchbauer, Gerhard (Flavour and fragrance journal, 2012)
The antimicrobial activity of essential oils is discussed in this review taking in account studies which were published in the period of time from 2008 until September 2010. Furthermore, the most important methods to examine the antimicrobial efficiency of essential oils are presented. The studies are divided into the following two groups, namely antibacterial and antifungal active agents depending on the activity of the applied essential oil against the test microorganisms. Various interesting possible applications are revealed such as the use of essential oils instead of synthetic drugs to circumvent the increasing resistance of some pathogens. Moreover, they could not only be used for the therapy of infectious illnesses, but also as preservatives in the food industry. A further possibility is, among others, the application of essential oils in skin products in order to treat or avoid dermal infections. Additionally, the prevalent constituents of the individual antimicrobial active essential oils are elaborated.